TEKST JAKO TERAPIA. HUMANISTYKA MEDYCZNA... / Text as Therapy. Medical Humanities and Studies of Experience and Its Representation in Contemporary Polish Literary Culture (An Introduction to an Interdisciplinary Field of Research) - Muca, Klaudia (Prace Polonistyczne, 2019)
This study presents a critical analysis of the discursive sphere of interdisciplinary interaction between broadly understood textual studies, including studies of representation and literary criticism, and medical humanities. The article critically reconsiders the interpretative paradigm of text as (self-)therapy. The paradigm dominated the discourse of medial humanities, especially in the field of narrative medicine and is deeply rooted in literary studies of illness and disability narratives in Poland. While the paradigm is seen as a neutral scheme of interpretation in contemporary literary studies and medical humanities, it seems that it somewhat narrows down and reduces the scope of possible interpretations of experience-oriented texts (i.e. texts that create, represent, and validate a particular personal or communal experience), and especially the interpretations that reach beyond the texts towards activism and emancipation.